Exhaled propofol monitoring for plasma drug prediction in rats - Li, Xiaoxiao; Chang, Pan; Liu, Xing; Kang, Yi; Zhao, Zhongjun; Duan, Yixiang; Zhang, Wensheng (Frontiers in Veterinary Science, 2025)
While propofol can be detected in exhaled breath in rats, robust evidence supporting its correlation with plasma concentrations or its use in predicting plasma levels remains lacking. In this study, eighteen mechanically ventilated rats were divided into three groups and injected with low (Group BL, n = 6), medium (Group BM, n = 6), or high (Group BH, n = 6) doses of propofol. The propofol concentration in exhaled breath (Ce-pro) was determined online using vacuum ultraviolet time-of-flight mass spectrometry (VUV-TOF MS), while the propofol concentration in plasma (Cp-pro) were measured using high-performance liquid chromatograph. The results indicated that after propofol injection, the peak Ce-pro was 5.87 ± 1.67 ppbv, 16.54 ± 7.22 ppbv, and 25.40 ± 3.68 ppbv, respectively. Across the different dose groups, Cmax of Ce-pro and Cp-pro were linearly correlated (PBL = 0.032, PBM = 0.031, PBH = 0.049). Tmax of Ce-pro was 1.22 ± 0.17 min, 1.28 ± 0.13 min, and 1.33 ± 0.01 min, respectively (P = 0.341), similar to the Tmax of Cp-pro (1.00 ± 0.00 min). After natural logarithm transformation, the correlation between LN(Ce-pro) and LN(Cp-pro) was well fitted by a linear model, with RBL2 = 0.94, RBM2 = 0.95, RBH2 = 0.98, and RALL2 = 0.96. Using the obtained regression equation LN(Cp-pro) = 1.42*LN(Ce-pro)-1.70, the predicted Cp-pro values showed excellent agreement with the actual values within groups (ICCBL = 0.92; ICCBM = 0.97, ICCBH = 0.99, all P < 0.001). This study demonstrates a strong correlation between exhaled and plasma propofol concentrations in rats, indicating that exhaled concentrations can be effectively used to estimate plasma levels.